Weighty Matters: The Obesity–Thyroid Nodule Connection Unveiling the Impact of Obesity on Thyroid Cancer Risk - Saad M. Alqahtani; Bassam A. Altalhi; Yousef S. Alalawi; Areej A. AlFattani; Saif S. Al-Sobhi (Medicina, 2023)
Background and Objectives: The effect of obesity on the development/progression of thyroid nodules with uncertain cytology is unknown. Therefore, our objective was to assess the role of body mass index (BMI) in predicting malignancy in patients with atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) nodules. Materials and Methods: We retrospectively analyzed 113 patients with available BMI data and final histopathology of benign or differentiated thyroid cancer. Patients were classified into four groups based on BMI: <18.5 (underweight), 18.5–24.9 (normal weight), 25–29.9 (overweight), and ≥30 (obesity) kg/m2. The association between risk of malignancy and BMI was examined for all data and subgroups based on nodule size, sex, and age. Results: Overall, 44.2% were obese, 36.3% were ≥45 years, and 75.4% were women. Final pathological results showed malignant nodules in 52 patients (46%) and benign nodules in 61 patients (54%) (mean age: 41 ± 11.6 vs. 39.9 ± 11.7 years; p = 0.62). Men had more malignant nodules than benign nodules (32.7% vs. 16.4%, p < 0.05). Overall, no significant correlation was identified between the risk of thyroid cancer and BMI, and the risk of malignancy was not significantly different between obese men and women (p = 0.4). However, in individuals with BMI < 30 kg/m2 (non-obese group), malignant nodules were more frequent in men than in women (71% vs. 41%, p = 0.04). No significant difference was observed in mean nodule size between the benign and malignant groups. Furthermore, BMI was not related to increased risk of malignancy in multiple logistic regression models using all data, even after controlling for confounding variables (odds ratio, 0.99, 95% confidence interval: 0.93–1.06, p = 0.87) or when stratifying by sex. Conclusions: Our study showed no correlation between obesity and thyroid cancer in patients with AUS/FLUS. Moreover, men had more malignant nodules than benign nodules. Further well-designed prospective studies are required to confirm our findings.